Promoting freedom in education. Study of a case. - Gregòri, Salvador Peiró i (Advances in Social Sciences Research Journal, 2018)
Contextualized the value "freedom" in relation to current problems, the liberty’s and various ways of conceiving freedom is defined, as well as the demands that their metaphysics and anthropology demand. Then it is interpreted in relation to human rights and other values, human and social virtues, etc., pointing out the way of presenting values’ freedom in schools’ conflict. Then the main models and procedures to promote them are considered, with the possible curricular derivations. The aims are related with the followed heuristic issues: a) How to teach humanitarian principles? b) How to promote Human Rights? c) What issues and values are promoted through the curriculum? d) Related to freedom, what issues & values are promoted? e) Are there contradictions in the teachings? f) Is it possible to implement this model? g) Is it possible to carry out such a model-value? The method of research is analytical, transversal case study, without sample type and size, taking advantage of only the opportunity to interview. But, before a phenomenological and hermeneutical procedure was made, configuring a network to interpret axiological skills results’ for the questionnaire’s items. The population had surveyed wear teachers and students. The distribution by years/population is as follows: 2008: 1130, 2009: 995, 2010: 1468, 2011: 959. With a questionnaire, a provincial reality is analytical-empirically studied. Defining the model as proceduralist, proposals to supplement it are offered. Main conclusions: The issues and values related with freedom are promoted through the curriculum are consistent with the statements mentioned in the theoretical framework. The results of teaching and learning do not remain in mere rational exercise. The teaching of peace are understood in the curriculum does not follow that it develops more personalizing than intellectual. The found model is largely procedural. The education for full freedom is not complete, because it is not clear that there are content with human values. On Human Rights’ education, there is a certain ambiguity between the transversal and notional of values and themes. Teaching the curriculum development is insufficient, so it shall be possible to implement an integrated model.